ROBOTIC ARM CONTROL SYSTEM DESIGN FOR HIGH PRECISION WORK - Enda Wista Sinuraya; Bambang Winardi; Zain Nizam (Journal of Moeslim Research Technik, 2025)
The demand for high-precision tasks in various industries, such as manufacturing and healthcare, necessitates the development of advanced robotic systems. Traditional robotic arms often struggle to meet the accuracy and repeatability required for precision work. This research focuses on designing a control system specifically tailored for robotic arms to enhance their performance in high-precision applications. The primary goal of this study is to develop an advanced control system for robotic arms that improves accuracy and reliability during precision tasks. The research aims to evaluate the effectiveness of various control algorithms in optimizing the performance of the robotic arm. A systematic approach was employed, utilizing simulation software to design and test different control strategies, including PID control and adaptive control methods. Performance metrics such as positional accuracy, response time, and stability were analyzed through a series of experiments conducted in both simulated and real-world environments. The implementation of the advanced control system resulted in significant improvements in the robotic arm's performance. The adaptive control method achieved a positional accuracy of 0.1 mm, with a response time reduction of 30% compared to traditional PID control. These findings demonstrate the effectiveness of the proposed control strategies in enhancing precision. The research successfully developed a robust control system for robotic arms, significantly improving their ability to perform high-precision tasks.